Hedge and central pruning in a high-density pecan orchard in southern Brazil - Hellwig, Cristiano Geremias; Martins, Carlos Roberto; Vaz Lima, Antonio Davi; Farias Barreto, Caroline; Farias Medeiros, Julio Cesar; Barbosa Malgarim, Marcelo (Comunicata Scientiae, 2022)
This study aimed at evaluating the influence of two pruning methods, as well as absence of pruning, on vegetative and productive development and in the quality of pecan fruits in a high-density orchard. The experiment was conducted with the cultivar Melhorada in a commercial pecan orchard in municipality of Santa Rosa, Rio Grande do Sul (RS), Brazil. The study was carried out between July 2018 and June 2020. In a randomized block design, the following treatments were applied: no pruning, hedge pruning and central pruning. Hedge pruning increased limb growth, while central pruning decreased the number of dry branches. Fruit production oscillated in the cycles. In the first, production was higher when central pruning was conducted. In the second cycle, it was higher in unpruned trees. Even though both pruning methods decreased the number of fruit with closed epicarps, they did not affect most variables of fruit quality. Therefore, results show that pruning methods promote vegetative development of pecan trees, reducing dry branches, but they are inconclusive regarding their production and have no significant effect on the main variables of their fruit quality. The evaluation and continuity of pruning for more cycles is important to obtain the most consistent results for indicating the best alternative for producers.